Debt spillovers in a monetary union: A novel rationale for central bank independence - Juan C. Campoy-Mi\~narro; Juan Carlos Negrete (Economics: The Open-Access, Open-Assessment Journal, 2022)
Central bank independence has been championed on the grounds that it avoids political business cycles, the time-inconsistency problem of discretionary monetary policy, and political conflicts. However, after the financial crisis, central banks have resorted to unconventional monetary policies and embraced additional tasks, making monetary authorities more exposed to political interference. This new reality has put into question the long-lasting consensus on the desirability of central bank independence. We add to this debate a new argument in support of that independence, namely, it internalizes the fiscal spillovers that arise in a monetary union, which is not a full fiscal union.
Keywords: E52; E58; 330; Central Bank design; fiscal policies; international fiscal spillovers; monetary union